Foreign activity effects on the capital structure of Brazilian companies during 2004-2008 - Hiramoto, Eduardo (2010)
Do Brazilian companies with foreign activities (M C) have different capital structure from domestic companies (DC)? If so, is the upstream-downstream hypothesis prediction valid, with internationalized companies using more debt than domestic corporations? We found that Brazilian M Cs use more debt due to international activity, with 9.6% more leverage, from which 5.8% come from long-term sources. We also shed some light on an alternative explanation for higher debt usage by internationalized companies. This dissertation tests whether there is a link between international activity and foreign debt financing. Does the access to foreign debt help to explain why M Cs use more debt than DCs? Our results show that international activity is positively related to foreign debt usage, and average M Cs carries 12.7% more foreign debt in their capital structure. Our sample consists of 131 companies within the period from 2004-2008, resulting in 538 firm-year observations.